The Digital Turn in Religious Studies: Research, Services, Infrastructures - Melloni, Alberto (V&R Unipress, 2025)
The adoption of new technological paradigms has recently shifted part of the scholarship on religions towards new research questions.Such a new condition stimulates scholarly curiosity which needs to be effective and fertile matching with technological infrastructures and access to physical and digital sources and research means.